2020
DOI: 10.3390/ijms21072320
|View full text |Cite
|
Sign up to set email alerts
|

Using Phosphatidylinositol Phosphorylation as Markers for Hyperglycemic Related Breast Cancer

Abstract: Studies have suggested that type 2 diabetes (T2D) is associated with a higher incidence of breast cancer and related mortality rates. T2D postmenopausal women have an ~20% increased chance of developing breast cancer, and women with T2D and breast cancer have a 50% increase in mortality compared to breast cancer patients without diabetes. This correlation has been attributed to the general activation of insulin receptor signaling, glucose metabolism, phosphatidylinositol (PI) kinases, and growth pathways. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 122 publications
(127 reference statements)
1
3
0
Order By: Relevance
“…This shows that our method is effective and practical. By means of enrichment analysis using GO and KEGG, we found that these risk lncRNAs are significantly enriched in cancer-related biological processes and pathways, which have been stated by researchers (Hamilton and Infante, 2016;Anwar et al, 2018;Devanathan et al, 2020;Saeidi et al, 2020), and we found that the regulation of risk lncRNAs on BRCA-related genes is synergistic rather than alone. As a result, we found that these 30 risk lncRNAs are highly correlated with the occurrence and development of BRCA, and they may form the network system to jointly regulate the initiation and course of BRCA.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This shows that our method is effective and practical. By means of enrichment analysis using GO and KEGG, we found that these risk lncRNAs are significantly enriched in cancer-related biological processes and pathways, which have been stated by researchers (Hamilton and Infante, 2016;Anwar et al, 2018;Devanathan et al, 2020;Saeidi et al, 2020), and we found that the regulation of risk lncRNAs on BRCA-related genes is synergistic rather than alone. As a result, we found that these 30 risk lncRNAs are highly correlated with the occurrence and development of BRCA, and they may form the network system to jointly regulate the initiation and course of BRCA.…”
Section: Discussionsupporting
confidence: 69%
“…The study indicated that Ras which is upregulated in BRCA can promote BRCA cell proliferation, migration, and invasion due to their capability to alter integrinmediated cell adhesion (Di et al, 2015). For the biological processes, PI3K is the most common altered pathway in ERpositive BRCA and PI3K/AKT is one of the most critical signal pathways for cancer (Hamilton and Infante, 2016;Devanathan et al, 2020). These results recommended that the three lncRNAs with higher degree, betweenness, and closeness were important in the network and played a crucial role in the origin and development of BRCA.…”
Section: Topological Analysis Of Slgcenbcmentioning
confidence: 99%
“…Interestingly, PI-3-K/AKT signaling can be activated by estrogen (ER), progesterone (PR), and HER2 thereby regulating the breast cancer cell signaling network. On the other hand, PI-3-K has also been associated with a mechanism of immune resistance in breast cancer, and over-expression of the p110β isoform of PI-3-K has been shown to inhibit the motility of breast cancer cells. , …”
Section: Resultsmentioning
confidence: 99%
“…It seems to be this is one of the reasons that insulin therapy causes increased mortality in MM patients who had pre-existing or steroid-induced T2DM [19]. Indeed it was revealed that prolonged high-glucose exposure leads to the blockage or change of the different cell signaling [57][58][59][60][61].…”
Section: Effects Of Ins On the Cas-3 And Bcl-2 Mrna Expression Levelsmentioning
confidence: 99%